Comprehensive performance measurement system and job performance : influence of role stress, organisational commitment and locus of control / Zarinah Abdul Rasit - Abdul Rasit, Zarinah (2013)
Prior research has highlighted the limitations of traditional management control and performance measurement systems (PMS) whereby the systems were claimed to be inadequate for today’s business environment. The shortcomings of traditional PMS have led to the use of more comprehensive PMS. Extant research indicates Comprehensive Performance Measurement System (CPMS) is widely used in organisations for decision facilitating and influencing purposes. Empirical evidences also show that the number of companies adopting multiple PMS (i.e. Balanced Scorecard) for performance measurement and evaluation is increasing. However, recent research provides inconsistent findings on the relationship between the use of CPMS and performance. These findings imply that CPMS may not necessarily lead to better performance, as the effectiveness of CPMS could be subjected to the limitation in the manager’s cognitive abilities. In particular, the research in the context of evaluative judgement implies that there are drawbacks from CPMS as there are limitations in the manager’s cognitive abilities. Information could be overloaded due to variations or too many measures used in a CPMS. Review of the literature suggests that research that examines behavioural consequences of the informational characteristics of CPMS is lacking suggesting there may be an indirect relationship between CPMS and performance. Drawing from this gap in the literature, using cognitive motivational theory, this research examines whether the link between CPMS and job performance is influenced by role stress, organisational commitment and locus of control. This research will also contribute to provide further understanding of the effect of MAS, in the context of PMS on individual performance. Specifically, this research proposes that CPMS may affect job performance via mediating variables of role stress (role ambiguity and role conflict) and organisation commitment (affective commitment). Based on the social learning theory, this research also predicts that a manager’s personality of traits, locus of control (internal and external manager) influences the relationship between the decision-facilitating role of CPMS and job performance. Data were collected using questionnaire survey and interviews. The sample comprised business unit (BU) managers of manufacturing companies, members of the Federation of Malaysian Manufacturer (FMM). Based on useable survey responses of 120 business unit managers, the results show the role ambiguity (role stress dimension) and organisational commitment mediate the relationship between CPMS and job performance. However, there is no evidence on the mediation effect of role conflict in the relationship. This implies CPMS will enhance job performance through the presence of high level of organisational commitment and lower role ambiguity. The moderation effect of locus of control is only identified in the relationship between CPMS and role ambiguity. However, no support was found for the moderating effects of locus of control in each relation between CPMS and organisational commitment, role conflict and job performance. Finding implies manager’s locus of control personality influence the use of PMS information and behaviour. Particularly, internal managers who perceive that they are in control of their performance will have higher motivation, thus would perform better than external manager. The interview results provide further insights and support for the survey findings. Role ambiguity and organisational commitment play important role in the use of CPMS to improve job performance. There is evidence indicating managers’ locus of control personality influence the use of CPMS and managers’ behaviour.